PKM Community Empowerment and Application of Plastic Waste Treatment Technology in Nelayan Village, Mayangan, Legonkulon, Subang - Adhan Efendi; Muhammad Iqbal; Ade Nuraeni; Yohanes Sinung Nugroho (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Community service activities are in the form of making tools and assistance in building clean and comfortable villages and reducing the risk of flooding due to accumulation of garbage in the coastal watershed (DAP) Mayangan Village, Legon Kulon District, Subang Regency, West Java Province. 12 August – 30 September 2021. The results of this community service are plastic waste processing machines and the formation of youth who care about waste in Mayangan Village. The results of this community service conclude that (1) the coastal watershed (DAP) environment is clean of plastic waste; (2) training on waste management and the dangers of waste is carried out to increase public awareness of the dangers of plastic waste; (3) plastic waste processing equipment is expected to reduce waste that causes flooding.